INSIDER THREATS: PROFILING POTENTIAL MALICIOUS ATTACKS, SEVERITY AND IMPACT - Ibrahim Z.-A.; Rahim F.A.; Alauddin A.A.; Jamil N.; Abdullah H.I.M. (Little Lion Scientific, 2023)
The insider threat that organizations and cooperation face today is a real and serious issue that has become increasingly difficult to address as time has passed. More complex approaches must be researched and developed for reliable recognition, detection, and response to insider threats. One way to achieve this is by identifying and classifying diverse viewpoints of insider threats. Various studies focused on comprehending and mitigating insider threats by developing different taxonomies and terminologies relating to insiders, insider threats, and insider attacks. However, few are concerned about the severity and impact of insider threats to an organization. Therefore, this paper proposes a taxonomy for profiling potential malicious attacks, highlighting severity to determine the impact of insider threats and the prioritization of vulnerability remediation activities. 2022 Little Lion Scientific